2001
DOI: 10.1097/00000374-200108000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Origins and Consequences of Age at First Drink. I. Associations With Substance-Use Disorders, Disinhibitory Behavior and Psychopathology, and P3 Amplitude

Abstract: Our findings indicated that AFD is not specifically associated with alcoholism but rather is correlated with a broad range of indicators of disinhibited behavior and psychopathology. Moreover, individuals who first drink at a relatively early age manifest elevated rates of disinhibitory behavior and psychopathology before they first try alcohol. Taken together, these findings suggest that the association of AFD with alcoholism reflects, at least in part, a common underlying vulnerability to disinhibitory behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
149
2
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(164 citation statements)
references
References 43 publications
(21 reference statements)
12
149
2
1
Order By: Relevance
“…Data from the Minnesota Twin Family Study revealed that girls and boys who reported drinking before age 14 scored between .2 and .5 standard deviations above nondrinkers on teacher-rated measures of opposition, hyperactivity, impulsivity, and inattention (McGue, Iacono, Legrand, Malone, & Elkins, 2001). Findings from a sample of alcohol-abusing or alcohol dependent and comparison adolescents revealed significantly higher levels of selfreported impulsivity and aggression among both male and female problem drinkers (Solof et al, 2000).…”
Section: Behavioral Under-controlmentioning
confidence: 92%
“…Data from the Minnesota Twin Family Study revealed that girls and boys who reported drinking before age 14 scored between .2 and .5 standard deviations above nondrinkers on teacher-rated measures of opposition, hyperactivity, impulsivity, and inattention (McGue, Iacono, Legrand, Malone, & Elkins, 2001). Findings from a sample of alcohol-abusing or alcohol dependent and comparison adolescents revealed significantly higher levels of selfreported impulsivity and aggression among both male and female problem drinkers (Solof et al, 2000).…”
Section: Behavioral Under-controlmentioning
confidence: 92%
“…Other risk factors may be in domains other than substance use. In this issue, McGue and colleagues extend their work on shared liability to substance use and externalizing in adolescence (e.g., McGue et al 2001) to examine the genetic and environmental overlap between problem behaviors in adolescence and risk for adult substance abuse. Dick and colleagues (this issue) describe how variation at a specific genetic locus (GA-BRA2) may influence conduct disorder in adolescence but alcohol and drug dependence in adulthood.…”
Section: Challenges For Genetic Research On Substance Usementioning
confidence: 99%
“…The papers reflect several themes, including genetic influences on stages of substance involvement (Pagan et al 2006;Lessem et al 2006;Neale et al 2006;VargasIrwin et al 2006), factors which predict adult substance related problems (Dick et al 2006;McGue et al 2006;Lessem et al 2006), and measurement and other methodological issues in substance abuse genetics (Crabbe et al 2006;Agrawal et al 2006;Pergadia et al 2006;Neale et al 2006). Five of the papers examine risk factors that extend across classes of substances (Lessem et al 2006;McGue et al 2006;Young et al 2006;Neale et al 2006;Dick et al 2006), whereas the others focus on a specific substance class, including alcohol (Pagan et al 2006;Crabbe et al 2006), tobacco Pergadia et al 2006), and cocaine (Vargas-Irwin et al 2006).…”
Section: Overview Of the Special Issuementioning
confidence: 99%
“…Although the development of substance use disorders (SUD) in adolescence is less prevalent, it is not rare (Kandel et al, 1997;Young et al, 2002), and early onset of use is a well-established risk factor for the progression from use to abuse and dependence (Bucholz et al, 2000;Chen and Anthony, 2003;Grant and Dawson, 1998). It has been argued that this trajectory may be a by-product of an underlying pattern of disinhibitory psychopathology rather than a direct risk (McGue et al, 2001).…”
Section: Introductionmentioning
confidence: 99%